2021
DOI: 10.1098/rspb.2020.2848
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of honest reward signal in flowers

Abstract: Some flowering plants signal the abundance of their rewards by changing their flower colour, scent or other floral traits as rewards are depleted. These floral trait changes can be regarded as honest signals of reward states for pollinators. Previous studies have hypothesized that these signals are used to maintain plant-level attractiveness to pollinators, but the evolutionary conditions leading to the development of honest signals have not been well investigated from a theoretical basis. We examined conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…6 A and B ; SI Appendix , Table S1 ). These cumulative results strongly suggest that nesocodin’s red color is both visible and attractive to Phelsuma day geckos, thus supporting a role in pollinator attraction as a conspicuous “honest reward,” as previously suggested ( 10 , 11 , 24 , 25 ).…”
Section: Nesocodin Is Visible and Attractive To Day Geckossupporting
confidence: 82%
“…6 A and B ; SI Appendix , Table S1 ). These cumulative results strongly suggest that nesocodin’s red color is both visible and attractive to Phelsuma day geckos, thus supporting a role in pollinator attraction as a conspicuous “honest reward,” as previously suggested ( 10 , 11 , 24 , 25 ).…”
Section: Nesocodin Is Visible and Attractive To Day Geckossupporting
confidence: 82%
“…This may be best exemplified by the convergent evolution of floral colour change producing a combination of extended flower life and colour change in old, rewardless flowers (Weiss, 1995 ; Ohashi et al ., 2015 ; Figs 4C , 6A ). In particular, a theoretical study has confirmed that the trait combination in floral colour change becomes evolutionarily stable only in generalized systems where both opportunistic and well‐informed pollinators visit (Ito, Suzuki & Mochizuki, 2021 ). Recent studies have also revealed that species in Melastomataceae have undergone convergent and correlated evolution of multiple floral characters in association with generalized pollination systems (Dellinger et al ., 2019 a ; Gavrutenko et al ., 2020 ).…”
Section: Future Perspectives For Investigating Trade‐offs In Flower–visitor Relationshipsmentioning
confidence: 99%
“…Although using hyperspectral remote sensing to study vegetation is relatively novel compared to the use of multispectral remote sensing, advancements in this field may be critical to capturing the health and flowering dynamics of different species at fine spatial and temporal grain. This may facilitate detecting changes in flowering over short periods of time and corresponding shifts to floral rewards, which can influence pollinators' foraging decisions (Ito et al, 2021). Furthermore, some studies have used hyperspectral datasets to establish relationships between species biodiversity and spectral diversity.…”
Section: Discussionmentioning
confidence: 99%